Z problematyki podmiotów prawa cywilnego i praw podmiotowych prywatnych obywateli polskich w Generalnym Gubernatorstwie - Górnicki, Leonard (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article deals with the issues of civil law entities and private rights of Polish citizens in the General Government (Generalgouvernement für die besetzten polnischen Gebiete), existing from 1939 to 1945. Having outlined the concept and reality of the General Government as a Reststaat, the author shows that the separate legal situation of the individual national groups (their national status, racial status) living in the General Government, in violation of the principle of equality in law, has affected many civil law relationships. The following issues are analyzed successively: the right to marry and have sexual relations, violation of the autonomy of the will regarding the right to work, limitations of the autonomy of the will of the subject of the law and the legal position in the professional sphere, and finally, discrimination against the Jewish population as subjects of private law. The author proves that the Polish legislation was applied to the Polish population in the scope of civil law that is of interest to us here, but it was significantly changed or repealed by the legislation of the General Government. Since the individuality of the person has become an essential element of private law, the sphere in which the subject of the law has freely regulated legal situations created by acts of his or her own will has become increasingly narrowed. Furthermore, even more specifically, the sphere of private individuals’ legal rights, traditionally protected by civil law, has been diminishing. The effect of national and racial discrimination against Poles was inextricably linked to the aspect of economic exploitation, which was fundamental for the interests of the Third Reich. From the very beginning, however, the occupier’s primary goal in relation to the Jewish population was to deprive Jews of their personal dignity, to stigmatize them, humiliate them, break their will to resist, force them to be obedient, economically exploit them, ”destroy them by work”, and finally exterminate the entire nation.
Keywords: The General Government; civil law; national status; racial status; violation of the principle of equality in law; violation of the autonomy of the will of a subject of private law; discrimination against the Jewish population as subjects of private law